Atomic-level flatness on oxygen-free copper surface in lapping and chemical mechanical polishing. Issue 20 (22nd August 2022) - Liu, Dongdong; Zhang, Zhenyu; Feng, Jiajian; Yu, Zhibin; Meng, Fanning; Xu, Guanghong; Wang, Jianmei; Wen, Wei; Liu, Wei
Abstract : Schematic diagram of chemical mechanical polishing on oxygen-free copper: (a) the pristine surface prior to CMP, (b) the chemical reaction, (c) mechanical removal and (d) atomic-level ultra-smooth surface after CMP. Abstract : Oxygen-free copper (OFC) serves as a core component of high-end manufacturing, and requires high surface quality. It is always a significant challenge to manufacture high-quality atomic-level surfaces. In this study, SiO2 nanospheres with good dispersibility were prepared and a late-model environmentally friendly chemical mechanical polishing (CMP) slurry was developed. The CMP slurry consists of SiO2 nanospheres, CeO2 nanospheres, H2 O2, NaHCO3, polyaspartic acid and deionized water. After CMP, the average roughness (Sa) of the OFC wafer reached 0.092 nm with an area of 50 × 50 μm 2 . Atomic-level flatness on the oxygen-free copper surface was acquired, which has never been reported before. Moreover, the mechanical removal mechanism of abrasive particles and the chemical reactions during lapping and CMP are proposed in detail. The thickness and composition of the damaged layer after lapping and polishing were analyzed. The lapping-damaged layer consists of a lattice distortion region, moiré fringes, grain boundary, superlattice and edge dislocations, and the polishing-damaged layer contains a handful of stacking faults with single-layer or multi-layer atoms. The chemical action involves three reactions: oxidation, corrosion and chelation. The processing method and its mechanistic explanation pave the way for the fabrication of high-performance OFC surfaces for use in vacuum, aerospace, military and electronic industries.